Anthropoaesthetics of Expression. Art and Knowledge in Friedrich Schleiermacher - Tenti, Gregorio (Aesthetica Preprint, 2021)
At the core of Friedrich Schleiermacher’s theory of individuality lies the concept of expression. From his early writings to his last lessons, Schleiermacher described an ever-manifesting individual, revolving around a dynamic connection to the foundational whole of universal forces. In his view, to produce individual knowledge means to align with such forces in a concretely singular way: it is the case of artistic knowledge, regarded as a process of manifestation of an interiorly resonating becoming. This paper aims at analysing the role of expressive knowledge in Schleiermacher’s philosophy, with special regard to his aesthetics and to the concept of Trieb (impulse). The particular presence of an anthropological tone in his view will finally be indicated as an ‘anthropoaesthetic’ feature that characterizes the Moravian philosopher’s thought.